Oscillations in cardiovascular function during acute hypoxia in the newborn piglet are associated with less neurological damage and occur more frequently in females - Harris, T.; Healy, Genevieve; Colditz, P.; Lingwood, B. (Wolters Kluwer Health, 2009)
The function of the cardiovascular system during hypoxia is an important determinant of neurologic outcome. Oscillations in blood pressure, particularly type-3 waves with a duration of 10 to 160 s, have been shown to occur in the presence of hypoxia in the neonatal rat. The aim of this study was to determine the characteristics and occurrence of type-3 waves in the neonatal piglet and any relationship to neurologic damage after acute global hypoxia. Hypoxia/hypercarbia was induced in 32 anesthetized piglets by reducing the fraction of inspired oxygen to 0.1 and the ventilation rate from 30 to 10 breaths per minute for 45 min. The degree of neurologic damage was assessed using both physiologic (EEG amplitude and cerebral impedance at 6 h posthypoxia) and structural (microtubule associated protein-2 immunohistochemistry) markers. Type-3 waves in cardiovascular function occurred in 56% of animals. An oscillating pattern was significantly associated with less neurologic damage (p = 0.01) and a lower duration of hypotension during hypoxia (p = 0.02), and occurred more frequently in females (p = 0.024). Copyright © 2009 International Pediatric Research Foundation, Inc.